2022
DOI: 10.1186/s12870-022-03598-6
|View full text |Cite
|
Sign up to set email alerts
|

Variations of subtelomeric tandem repeats and rDNA on chromosome 1RS arms in the genus Secale and 1BL.1RS translocations

Abstract: Background The wheat-rye 1BL.1RS translocations have played an important role in common wheat breeding programs. Subtelomeric tandem repeats have been often used to investigate polymorphisms of 1RS arms, but further research about their organizations on the 1RS chromosome is needed. Results 162 1RS arms from a wild rye species (Secale strictum) and six cultivated rye accessions (Secale cereale L.) (81 plants), 102 1BL.1RS and one 1AL.1RS translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Oligo-3A1 exhibited three intact signals in the middle of chromosome 5RL [28]. Probe Oligo-TaiI was found to have specific hybridization to the 1RS terminal region by ND-FISH [29]. In the present study, we found that the new Oligo-D01-135 had distinct hybridization in the NOR region of 1RS (Figure 2b).…”
Section: New Nd-fish Probes For Identifying Wheat-rye Chromosomessupporting
confidence: 56%
“…Oligo-3A1 exhibited three intact signals in the middle of chromosome 5RL [28]. Probe Oligo-TaiI was found to have specific hybridization to the 1RS terminal region by ND-FISH [29]. In the present study, we found that the new Oligo-D01-135 had distinct hybridization in the NOR region of 1RS (Figure 2b).…”
Section: New Nd-fish Probes For Identifying Wheat-rye Chromosomessupporting
confidence: 56%
“…New organizations of subtelomeric tandem repeats on 1RS were found, and they reflec ted new genetic variations of 1RS arms [3]. These 1RS arms might contain abundant allelic diver sity for agricultural traits.…”
Section: Resultsmentioning
confidence: 91%
“…Thus, recombination in interspecific chromosome as sociations could be promoted with the aim of transferring desirable agronomic traits from re lated genetic donor species into crops [2]. Additionally, recombination operates at subtelo meres and, as it happens in rye and wheat, ho mologous recognition and pairing are more often correlated with the recombining regions than with the crossoverpoor regions [3].…”
Section: Introductionmentioning
confidence: 99%
“…Both of them are present in high copy numbers of tandem organized repetitive units in the genomes, and very often provide species-speci c patterns on chromosomes [e.g. 27,47,48,49,50].…”
Section: Introductionmentioning
confidence: 99%